Controller interface for web applications - Tan, Pin Che (Nanyang Technological University, 2022)
Smart+ is Kabam’s proprietary robotics software solution that provides a wide range of capabilities to their customers. These include remote teleoperation, monitoring, diagnosis and debugging. Currently they are suited for small to medium sized robots, including those in their lineup. There are plans to expand this functionality to forklifts, construction yard vehicles and construction equipment. Much work needs to be done to prepare Smart+ to be able to meet those goals. This includes improved features like teleoperation safety, intuitive controls, responsive controls, and fail safes. This project is the first step in the journey toward that goal and accomplishes the goals of teleoperation safety and intuitive controls to create a cockpit like experience of teleoperating vehicles remotely.